Analysis of the Impact of Electric Vehicle Technology on Reducing Greenhouse Gas Emissions - Rumiki, Exel; Axel, Jovan; Pitaloka, Cyntia Puspa (Universitas Ibn Khaldun Bogor, 2024)
One of the causes of increasing temperatures throughout the earth is the environmental impact resulting from exhaust from vehicles. This exploration is expected to determine the impact of the seeding system caused by mechanical vehicles. This exploration was carried out using written survey research techniques as clarification that could increase public information regarding the impact system of motor vehicle seeding. The seeding impact is the retention and removal of radiant energy from electromagnetic waves by gasses in the climate. The impact of seeding can prevent energy from sunlight from being reflected outside the earth. The impact of seeding can occur due to exhaust gasses, one of which is produced by motorized vehicles. Increased use of motorized vehicles can cause a rapid increase in smoke emissions. Because every motorized vehicle will emit smoke or ignition gas from the motorbike's combustion chamber. Vehicle engine exhaust emissions do not depend on how new or how old the vehicle is, but very much depend on the quality and maintenance of the vehicle engine. The rapid number of motorized vehicles is a consequence of the needs and demands of human existence. The outflow of motorized vehicles is also a major source of environmental pollution because they contain air pollution which is not good for human health.